Challenges Associated with the Roll-out of HCC Surveillance in Sub-Saharan Africa - the Case of Uganda - Hees, Stijn Van; Muyindike, Winnie; Erem, Geoffrey; Ocama, Ponsianoo; Seremba, Emmanuel; Apiyo, Paska; Michielsen, Peter; Okwir, Mark; Vanwolleghem, Thomas (Journal of Hepatology, 2020)
In their recent review article, Singal and coworkers describe the challenges associated with surveillance for hepatocellular carcinoma (HCC) and propose interventions to increase the effectiveness of surveillance. We agree with the authors that improved uptake of screening and performance of HCC surveillance should be considered a high priority in Western countries. In sub-Saharan Africa, where HBV infections are the main cause of HCC, surveillance programs are mostly not available. Nonetheless, with an incidence rate of 8.9 cases per 100,000 inhabitants per year, which is likely to be an underestimate, HCC surveillance is a pressing medical need in this part of the world. The recent introduction of country-wide vaccination programs in these countries will likely result in a drop in HCC incidence a few decades from now, but this does not apply to patients that are currently infected. In a recent African cohort of 1,315 hepatocellular tumors, 84% of the tumors were diagnosed at a late, multifocal disease stage with a mean size of 8 ± 4 cm and a median survival of 2.5 months.Given the strong association between early detection and improved survival, these findings highlight the need to set up surveillance programs in sub-Saharan Africa, provided curative treatment options are available.